EFFECT OF POVERTY ON HEALTHCARE ACCESSIBILITY AMONG PREGNANT WOMEN: A STUDY OF JINO COMMUNITY OF BATAGARAWA LOCAL GOVERNMENT AREA, KATSINA STATE, NIGERIA - Yauri, Muhammad Garba; Yakasai, Auwalu Sale (African Journal of Social and Behavioural Sciences, 2024)
This paper investigated the effect of poverty on healthcare accessibility among pregnant women in Batagarawa Local Government area, Katsina state. The Objectives of the study include assessing the correlation between poverty and healthcare availability, identifying barriers to accessibility to healthcare services, and understanding health outcomes in impoverished regions. The paper adopted a triangulation method of data collection that elicits information from primary sources. A total of 45 questionnaires were administered to generate qualitative data which were analysed using tables and simple percentages. In-depth interviews were also conducted with two residents, two healthcare providers and three community leaders. The vicious circle of poverty theory was used to guide the study. The findings revealed the effect of poverty on healthcare accessibility among pregnant women. Recommendations emphasized the necessity of targeted interventions, improved infrastructure, and community engagement to enhance healthcare accessibility in rural areas, mitigating the adverse effects of poverty on overall health outcomes.